Managing multiple business models: The role of interdependencies - Hendrik Harren; Dodo zu Knyphausen-Aufseß; Constantinos C. Markides (Schmalenbach Journal of Business Research (SBUR), 2022)
How can a~firm manage multiple and interdependent business models in the same industry? The literature has identified several possible strategies to do this but we still do not know under what circumstances one strategy may be better than others. Our paper identifies (substitute and complementary) interdependencies among business models as a~key contingency and demonstrates through simulation modelling that the number, type and magnitude of these interdependencies, as well as their visibility and the pre-specification of strategic choices, determine which organizational structure is optimal in managing multiple business models.
Keywords: 650; Activity Systems; Business Models; Interdependencies; Organizational Design; Simulation Methods